Double-sided adhesive tape

The double-sided adhesive tape, featuring a foam base material with optimized bubble structure and adhesive layers, addresses the challenges of increased shear loads and display unevenness in larger display devices, offering enhanced drop impact resistance and reworkability.

JP7667660B2Active Publication Date: 2025-04-23SEKISUI CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020571861
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-11-26
Publication Date
2025-04-23
Estimated Expiration
2040-11-26

AI Technical Summary

Technical Problem

Display devices such as televisions and monitors are becoming larger and heavier, leading to increased shear loads on adhesive tapes, which can result in interlayer breakdown or peeling due to impact during transportation. Additionally, there is a need for moderate flexibility in adhesive tape substrates to reduce display unevenness and allow for easy reworking of electronic components.

Method used

A double-sided adhesive tape with a foam base material and adhesive layers on both sides, where the foam base material has a foam volume fraction of 40% to 75% and a shear breaking strength of 200N/inch to 500N/inch. The bubble structure of the foam substrate is optimized using X-ray Computed Tomography and image analysis to enhance both strength and flexibility.

Benefits of technology

The adhesive tape achieves excellent drop impact resistance, reduces display unevenness, and allows easy tearing of the foam base material when peeling off, thereby facilitating reworking of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667660000003
    Figure 0007667660000003
  • Figure 0007667660000004
    Figure 0007667660000004
  • Figure 0007667660000005
    Figure 0007667660000005
Patent Text Reader

Abstract

The purpose of the present invention is to provide a double-sided pressure-sensitive adhesive tape which has excellent resistance to impacts by dropping and can reduce display unevenness in display devices and which includes a foam base that is easy to tear for removing from the adherend. This double-sided pressure-sensitive adhesive tape comprises a foam base and pressure-sensitive adhesive layers superposed on both surfaces of the foam base, wherein the foam base has a cell content of 40-75 vol% and a shear breaking strength of 200 N / inch2 to 500 N / inch2.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a double-sided pressure-sensitive adhesive tape. [Background technology]

[0002] Adhesive tapes are widely used for fixing electronic components. Specifically, for example, adhesive tapes are used for fixing the front cover panel to the housing of a display device such as a television or a monitor. Such adhesive tapes are used in a shape such as a picture frame and are arranged around the periphery of the display screen.

[0003] In recent years, as a result of the pursuit of design and functionality, the frames of display devices such as televisions and monitors have become narrower, and expectations for bezel-less display devices are also increasing. In the conventional manufacturing of display devices, the cover panel was sometimes fixed to the housing by fitting or screwing, but since fitting or screwing is difficult for display devices with narrower frames, there is an increasing demand for fixing with adhesive tape, and adhesive tapes are also becoming thinner and narrower.

[0004] As an example of an adhesive tape that can be used in such a display device, Patent Documents 1 and 2 describe an impact absorbing tape in which an acrylic adhesive layer is integrally laminated on at least one surface of a base layer, and the base layer is a cross-linked polyolefin resin foam sheet having a specific degree of cross-linking and aspect ratio of bubbles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-242541 A [Patent Document 2] JP 2009-258274 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, display devices such as televisions and monitors are becoming larger, and the weight of fixed members such as cover panels and housings is also increasing. As a result, the adhesive tape is subjected to a much larger load in the shear direction than before, and particularly when the adhesive tape is used in a thin and narrow width, there is a problem that interlayer destruction of the base material or peeling of the adhesive tape occurs due to impact caused by dropping during transportation. In addition, as display devices become larger, display unevenness is more likely to occur. In order to reduce display unevenness, the adhesive tape, especially the base material of the adhesive tape, is required to have appropriate flexibility to release stress. Furthermore, in recent years, electronic components have tended to become more expensive, so there is a demand for the components to be reworked when, for example, a defect occurs when fixing the components. One method for reworking components is, for example, a method in which the foam base material of the adhesive tape is torn with a cutter blade, causing interlayer destruction and removing the components. In such cases, the base material is also required to be not too hard and to have appropriate flexibility. Here, while it is necessary to increase the strength of the substrate in order to withstand impacts such as dropping during transportation, it is also necessary to increase the flexibility of the substrate in order to reduce display unevenness and make it easier to tear. However, since the strength and flexibility of the substrate are mutually exclusive properties, it is difficult to achieve both. The present invention aims to provide a double-sided pressure-sensitive adhesive tape that has excellent drop impact resistance, can reduce display unevenness on a display device, and has a foam base material that can be easily torn when peeled off from an adherend. [Means for solving the problem]

[0007] The present invention relates to a double-sided pressure-sensitive adhesive tape having a foam substrate and pressure-sensitive adhesive layers laminated on both sides of the foam substrate, the foam substrate having a bubble volume fraction of 40% by volume or more and 75% by volume or less and a shear breaking strength of 200 N / inch 2 More than 500N / inch 2 The double-sided adhesive tape is shown below. The present invention will be described in detail below.

[0008] The present inventors analyzed the bubble structure of the foam substrate in a double-sided adhesive tape having a foam substrate and adhesive layers laminated on both sides of the foam substrate using an X-ray CT (X-ray Computed Tomography) device and image analysis software, and investigated the effect of the bubble structure on the performance of the double-sided adhesive tape. As a result, the present inventors found that both the strength and flexibility of the foam substrate can be increased by adjusting the bubble volume fraction of the foam substrate to a specific range and further adjusting the shear breaking strength of the foam substrate to a specific range. As a result, it was found that a double-sided adhesive tape having excellent drop impact resistance, capable of reducing display unevenness of a display device, and capable of easily tearing the foam substrate when peeled off from an adherend can be obtained, and the present invention was completed.

[0009] The double-sided pressure-sensitive adhesive tape of the present invention has a foam substrate and pressure-sensitive adhesive layers laminated on both sides of the foam substrate. The foam substrate has an appropriate degree of flexibility and is therefore capable of releasing stress. By including the foam substrate, the stress relaxation properties of the double-sided pressure-sensitive adhesive tape are improved.

[0010] The foam base material has a bubble volume fraction of 40% by volume at the lower limit and 75% by volume at the upper limit. By adjusting the bubble volume fraction within the above range, it is possible to increase both the strength and flexibility of the foam base material and simultaneously achieve both. If the bubble volume fraction is 40% by volume or more, the foam substrate can have a suitable flexibility, so that display unevenness of a display device can be reduced, and the foam substrate can be easily torn when peeling off the double-sided adhesive tape from an adherend. If the bubble volume fraction is 75% by volume or less, the strength of the foam substrate can be prevented from being excessively reduced, so that the drop impact resistance of the double-sided adhesive tape can be improved. In addition, if the bubble volume fraction is 75% by volume or less, the dustproofness and waterproofness of the foam substrate can be easily ensured. The preferred lower limit of the bubble volume fraction is 42% by volume, the preferred upper limit is 70% by volume, the more preferred lower limit is 46% by volume, the more preferred upper limit is 67% by volume, the even more preferred lower limit is 48% by volume, the even more preferred upper limit is 63% by volume, the particularly preferred lower limit is 50% by volume, and the particularly preferred upper limit is 60% by volume. The bubble volume fraction is calculated by the following formula (1) using an X-ray CT apparatus and image analysis software. Air bubble volume fraction (volume%) = Air bubble volume / Volume of foam substrate × 100 (1) In formula (1), the cell volume is the total volume of all cells contained in the foam base material of the measurement sample.

[0011] The average and standard deviation of the major axis distribution of the cells in the foam base material are not particularly limited, but the preferred upper limit of the average of the major axis distribution of the cells is 55 μm, and the preferred upper limit of the standard deviation of the major axis distribution of the cells is 30 μm. By adjusting the average and standard deviation of the major axis distribution within the above ranges and suppressing the bubble size and the variation in bubble size to a certain level or less, it is possible to further increase both the strength and flexibility of the foam substrate, which results in improved drop impact resistance of the double-sided pressure-sensitive adhesive tape, reduced display unevenness of a display device, and easy tearing of the foam substrate when peeling the double-sided pressure-sensitive adhesive tape from an adherend. Furthermore, if the bubbles are too large or there is variation in bubble size, particularly when the double-sided pressure-sensitive adhesive tape is used in a thin and narrow width, the foam substrate will have locally weak spots, and when an impact is applied due to dropping during transportation, etc., interlayer destruction of the foam substrate or peeling of the double-sided pressure-sensitive adhesive tape will occur starting from these spots. By adjusting the average and standard deviation of the major axis distribution within the above ranges and suppressing the bubble size and the variation in bubble size to a certain level or less, it is possible to suppress the presence of locally weak spots and improve the drop impact resistance of the double-sided pressure-sensitive adhesive tape.

[0012] The upper limit of the average of the major axis distribution is more preferably 53 μm, even more preferably 51 μm, and even more preferably 49 μm. The lower limit of the average of the major axis distribution is not particularly limited and is determined depending on the cell volume fraction and thickness of the foam base material, but the substantial lower limit is 10 μm. The standard deviation of the major diameter distribution is more preferably 28 μm, even more preferably 27 μm, and still more preferably 24 μm. The lower limit of the standard deviation of the major diameter distribution is not particularly limited, and a smaller value is preferable because the size of the bubbles is more uniform. The substantial lower limit is 5 μm. The average and standard deviation of the bubble major axis distribution are determined using an X-ray CT scanner and image analysis software, and the average and standard deviation are calculated from the obtained major axis distribution.

[0013] The open cell ratio of the foam substrate is not particularly limited, but when the foam substrate is a polyurethane foam, the upper limit of the open cell ratio is preferably 95% by volume. Generally, polyurethane foams have an open cell structure, and the open cell ratio is close to 100% by volume. Therefore, when the foam substrate is a polyurethane foam, having an open cell ratio within the above range means that the open cell ratio is relatively low and there are many closed cells among polyurethane foams. By adjusting the open cell ratio within the above range and increasing the number of closed cells, it is possible to further increase both the strength and flexibility of the polyurethane foam, thereby improving the drop impact resistance of the double-sided pressure-sensitive adhesive tape, reducing display unevenness in a display device, and allowing the foam substrate to be easily torn when the double-sided pressure-sensitive adhesive tape is peeled off from an adherend. Furthermore, by adjusting the open cell ratio within the above range and increasing the number of closed cells, it is possible to suppress the presence of locally low strength areas as described above, and improve the drop impact resistance of the double-sided pressure-sensitive adhesive tape.

[0014] A more preferred upper limit of the open cell ratio is 93 volume %, and a further more preferred upper limit is 91 volume %. Although there are no particular limitations on the lower limit of the open cell ratio, the general lower limit of the open cell ratio of polyurethane foam is 90 volume %. The open cell ratio is calculated by the following formula (2) using an X-ray CT scanner and image analysis software. Open cell ratio (volume%) = open cell volume / cell volume x 100 (2) In formula (2), the interconnected cell volume is the total volume of all interconnected cells contained in the foam base material of the measurement sample, and the cell volume is the total volume of all cells contained in the foam base material of the measurement sample.

[0015] The flattening ratio of the cells of the foam substrate is not particularly limited, but a preferred upper limit is 0.2. By adjusting the flattening ratio within the above range, impact absorption against a drop from any angle can be more uniform, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape can be improved.

[0016] The upper limit of the flattening ratio is more preferably 0.18, still more preferably 0.16, and still more preferably 0.14. The lower limit of the flattening ratio is not particularly limited, and is preferably closer to 0 because the bubbles become closer to a perfect sphere and the impact absorption against a drop from any angle becomes more uniform, and the substantial lower limit is 0.05.

[0017] The aspect ratio of the cells of the foam substrate is not particularly limited, but a preferred upper limit is 1.5. By adjusting the aspect ratio within the above range, impact mitigation against a drop from any angle can be made more uniform, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape can be improved.

[0018] The upper limit of the aspect ratio is more preferably 1.1, even more preferably 1.09, and still more preferably 1.07. The lower limit of the aspect ratio is not particularly limited, and is preferably closer to 1 because the bubbles become closer to a perfect circle and the impact cushioning against a drop from any angle becomes more uniform, and the substantial lower limit is 1.01. The aspect ratio and flattening ratio of the bubbles are calculated using an X-ray CT scanner and image analysis software according to the following formulas (3) and (4). Aspect ratio=x / y (3) Oblateness={(x+y) / 2-z} / z (4) (x=long diameter, y=medium diameter, z=short diameter, x≧y≧z)

[0019] The X-ray CT apparatus and the image analysis software are not particularly limited, but more specifically, the analysis using the X-ray CT apparatus and the image analysis software is carried out, for example, as follows. The center of the measurement sample obtained by cutting the foam substrate is imaged using an X-ray CT device (e.g., Yamato Scientific Co., Ltd., "TDM1000H-II (2K)", resolution approximately 1.5 μm / 1 pixel) to obtain a rectangular 3D image of 1.5 mm in length, 1.2 mm in width, and 0.3 mm in height. The obtained image is subjected to noise removal and binarization using image analysis software (e.g., FEI Co., Ltd., "Avizo9.2.0") to obtain various values ​​representing the cellular structure of the foam substrate (cell volume fraction, average and standard deviation of the major axis distribution of the cells, open cell ratio of the cells, aspect ratio of the cells, and flattening ratio of the cells, etc.). Mo is used as the X-ray source, and the image is taken using a lens (L0270) under the conditions of binning 2, exposure time 10 seconds, and number of images taken 1200. When analyzing images, noise is first removed using the Median Filter (Neighborhood value 26) function. After that, binarization is performed using the Interactive Thresholding function. The threshold is set to 90 out of 256 gradations. In the binarized image, whether a bubble is an isolated bubble or an open bubble is determined by whether there is a break in the continuous part of the pixels. In addition, when calculating the long diameter, medium diameter, and short diameter, the bubbles are first divided at their contact points and the center of gravity of the bubble is found. Next, a rectangular parallelepiped is set with its center of gravity at the same position as the center of gravity and inscribed in the bubble, and the lengths of the three orthogonal sides are determined from the longest to the shortest as the long diameter, medium diameter, and short diameter, respectively. At this time, bubbles with a long diameter of less than 10 μm are excluded.

[0020] The method for adjusting each value representing the cell structure of the foam base material (cell volume fraction, average and standard deviation of the cell major axis distribution, open cell ratio, cell aspect ratio, cell oblateness, etc.) within the above range is not particularly limited. For example, when the foam substrate is a polyurethane foam, the types and contents of polyisocyanate and polyol in the urethane resin composition, the conditions for mixing air, nitrogen, etc. into the urethane resin composition, the reaction conditions for heat-curing the urethane resin composition, etc. may be adjusted. Among these, a method of slowly advancing the urethane reaction by increasing the content of polyisocyanate in the urethane resin composition to increase the fluidity of the resin, for example, to generate bubbles of a more uniform size and adjust the bubble structure is preferred. More specifically, the bubble volume fraction can be adjusted by changing the type and content of polyisocyanate and polyol in the urethane resin composition, and the foaming conditions. Even when the raw materials are the same, the bubble volume fraction can be adjusted by changing the conditions for mixing air, nitrogen, etc. into the urethane resin composition, the reaction conditions for heat curing the urethane resin composition, etc. In addition, the average and standard deviation of the major axis distribution of the bubbles can be reduced by slowly proceeding with the urethane reaction.

[0021] The foam substrate may have a single layer structure or a multi-layer structure. The foam base material is not particularly limited, and examples thereof include polyurethane foam, polyolefin foam, acrylic foam, etc. Among these, polyurethane foam is preferred because it has appropriate flexibility and the cell structure can be easily adjusted.

[0022] The polyurethane foam may be, for example, a polyurethane foam made of a urethane resin composition containing a polyisocyanate and a polyol. Such a polyurethane foam may be produced by heat curing the urethane resin composition. The polyisocyanate is not particularly limited, and examples thereof include aromatic polyisocyanates or aliphatic polyisocyanates that are generally used in polyurethane foams. Among these, aromatic diisocyanates or aliphatic diisocyanates having two isocyanate groups in one molecule are preferred.

[0023] When the polyisocyanate is an aromatic diisocyanate or an aliphatic diisocyanate, the degree of crosslinking of the polyurethane foam does not increase too much and the glass transition point (Tg) becomes relatively low, resulting in a foam that is easily stretched and has high strength and flexibility. Specific examples of the aromatic diisocyanate or aliphatic diisocyanate include 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,5-naphthalene diisocyanate, paraphenylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, m-xylene diisocyanate, hexamethylene diisocyanate, hydrogenated MDI, and isophorone diisocyanate. 4,4'-diphenylmethane diisocyanate is also generally called "MDI" or "binuclear monomeric MDI". Among these, 4,4'-diphenylmethane diisocyanate (MDI) is preferred because it is easy to obtain a polyurethane foam with excellent flexibility. These aromatic diisocyanates or aliphatic diisocyanates may be used alone or in combination of two or more kinds.

[0024] The polyisocyanate may have three or more isocyanate groups in one molecule. Examples of such polyisocyanates include polymeric MDI. Examples of the polyisocyanate further include urethane prepolymers having isocyanate groups. These polyisocyanates may be used alone or in combination of two or more.

[0025] The polyol is not particularly limited, and may be any polyol used in general polyurethane foams. Specific examples include polyether polyol, polyester polyol, polyether ester polyol, etc. In addition, the polyol may also include trifunctional polyether polyol, glycerin, trimethylolpropane, etc. These polyols may be used alone or in combination of two or more. The polyether polyol is not particularly limited, and examples thereof include polypropylene glycol (PPG), etc. The polyester polyol is not particularly limited, and polyester polyols composed of a polyol component and an acid component can be used.

[0026] The polyol preferably contains a short-chain diol. The polyol containing the short-chain diol increases the strength of the polyurethane foam, and therefore, even when the urethanization reaction is allowed to proceed slowly by increasing the content of the polyisocyanate in the urethane resin composition to increase the fluidity of the resin in order to generate bubbles of a more uniform size and adjust the cell structure, the strength of the polyurethane foam can be prevented from decreasing too much. Examples of the short-chain diol include 1,5-pentanediol, 1,6-hexamethylenediol, neopentyl glycol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, and neopentyl glycol. These short-chain diols may be used alone or in combination of two or more. Among them, 1,5-pentanediol or 1,6-hexamethylenediol is preferred because it is easy to obtain a high-strength polyurethane foam. In addition, neopentyl glycol is preferred because it is easy to reduce the open cell ratio.

[0027] The weight average molecular weight of the polyol is not particularly limited, but the preferred lower limit is 500 and the preferred upper limit is 5000. If the weight average molecular weight of the polyol is 500 or more, the polyurethane foam can have appropriate flexibility. If the weight average molecular weight of the polyol is 5000 or less, the strength of the polyurethane foam can be prevented from decreasing too much. The more preferred lower limit of the weight average molecular weight of the polyol is 700, the more preferred upper limit is 2000, the even more preferred lower limit is 800, and the even more preferred upper limit is 1500. The weight average molecular weight of the polyol can be measured, for example, by preparing a tetrahydrofuran solution of the sample and then using a GPC device (for example, Tosoh Corporation, product name "HLC-8220", column: TSKgelSurper HZM-N (4 columns)). In the GPC measurement, for example, the measurement conditions can be 40°C and a flow rate of 0.5 mL / min.

[0028] The isocyanate index of the polyisocyanate in the urethane resin composition is not particularly limited, but a preferred lower limit is 70 and a preferred upper limit is 120. The isocyanate index is an index related to the isocyanate equivalent in the reaction between an isocyanate and an active hydrogen-containing compound. When the isocyanate index is less than 100, reactive groups such as hydroxyl groups are in excess of isocyanate groups, and when the isocyanate index is more than 100, isocyanate groups are in excess of reactive groups such as hydroxyl groups. If the isocyanate index is 70 or more, crosslinking by the polyisocyanate is sufficient and the cell structure can be easily adjusted, so that the polyurethane foam can have an appropriate density and has high strength and flexibility.If the isocyanate index is 120 or less, the degree of crosslinking of the polyurethane foam is not too high and the glass transition point (Tg) is relatively low, so that the foam is easily stretched and has high strength and flexibility.

[0029] The content of the polyisocyanate in the urethane resin composition is not particularly limited. However, it is preferable to gradually advance the urethane reaction by increasing the content of the polyisocyanate in the urethane resin composition to increase the fluidity of the resin, thereby generating bubbles of a more uniform size and adjusting the bubble structure. The polyisocyanate content is preferably 5% by weight at the lower limit and 30% by weight at the upper limit relative to 100% by weight of the polyol. If the polyisocyanate content is 5% by weight or more, the urethane reaction can be allowed to proceed slowly to generate bubbles of a more uniform size, making it easier to adjust the bubble structure and increasing the strength and flexibility of the polyurethane foam. If the polyisocyanate content is 30% by weight or less, the degree of crosslinking of the polyurethane foam does not increase too much and the glass transition point (Tg) becomes relatively low, resulting in a foam that is easy to stretch and has high strength and flexibility. The more preferable lower limit of the polyisocyanate content is 15% by weight, and the more preferable upper limit is 25% by weight.

[0030] The urethane resin composition may contain a catalyst, if necessary. Examples of the catalyst include organic tin compounds, organic zinc compounds, organic nickel compounds, organic iron compounds, metal catalysts, tertiary amine catalysts, and organic acid salts. Among these, organic tin compounds are preferred. These catalysts may be used alone or in combination of two or more. The amount of the catalyst added is not particularly limited, but a preferred lower limit is 0.05 parts by weight, a preferred upper limit is 5.0 parts by weight, and a more preferred upper limit is 4.0 parts by weight, based on 100 parts by weight of the polyol.

[0031] Examples of the organotin compounds include stannous octoate, dibutyltin diacetate, and dibutyltin dilaurate. Examples of the organozinc compounds include zinc octylate. Examples of the organonickel compounds include nickel acetylacetoate and nickel diacetylacetoate. Examples of the organoiron compounds include iron acetylacetoate. Examples of the metal catalysts include alkoxides and phenoxides of alkali metals or alkaline earth metals such as sodium acetate. Examples of the tertiary amine catalysts include triethylamine, triethylenediamine, N-methylmorpholinedimethylaminomethylphenol, imidazole, and 1,8-diazabicyclo[5.4.0]undecene.

[0032] The urethane resin composition may contain a foaming agent as necessary. The foaming agent may be any foaming agent commonly used for polyurethane foams, such as water, pentane, cyclopentane, hexane, cyclohexane, dichloromethane, or carbon dioxide gas. The amount of the foaming agent added is not particularly limited and may be an appropriate amount, but when the foaming agent is water, it is usually about 0.1 to 3 parts by weight per 100 parts by weight of the polyol.

[0033] The urethane resin composition may contain a foam stabilizer, if necessary. The foam stabilizer may be, for example, a silicone-based foam stabilizer such as dimethylsiloxane, polyetherdimethylsiloxane, or phenylmethylsiloxane. Among them, polyetherdimethylsiloxane is preferred. Among polyetherdimethylsiloxane, a block copolymer of dimethylpolysiloxane and polyether is more preferred. These foam stabilizers may be used alone or in combination of two or more kinds. The amount of the foam stabilizer to be added is not particularly limited, but a preferred lower limit is 0.2 parts by weight, a preferred upper limit is 7 parts by weight, a more preferred lower limit is 0.4 parts by weight, and a more preferred upper limit is 5 parts by weight, relative to 100 parts by weight of the polyol.

[0034] The urethane resin composition may contain, as necessary, additives that are generally used in the production of polyurethane foams, such as an ultraviolet absorber, an antioxidant, an organic filler, an inorganic filler, a colorant, and the like.

[0035] Examples of methods for producing the polyurethane foam include a method (mechanical froth method) in which a urethane resin composition (liquid) obtained by mechanically mixing and foaming air, nitrogen, etc. is applied to the surface of a release liner or a resin film, and the applied urethane resin composition is heat cured to produce a foam. Other examples include a method (chemical foaming method) in which the polyisocyanate is reacted with a raw material for forming the polyurethane foam to generate a gas. Among these, the mechanical froth method is preferred. The polyurethane foam obtained by the mechanical froth method tends to have a higher density and a finer and more uniform cell structure than the polyurethane foam obtained by the chemical foaming method.

[0036] Examples of the polyolefin foam include foams made of resins such as polyethylene-based resins, polypropylene-based resins, polybutadiene-based resins, etc. Among these, polyethylene-based resins are preferred because they are easy to produce flexible polyolefin foams.

[0037] The foam base material has a lower limit of shear breaking strength of 200 N / inch 2 , upper limit is 500N / inch 2 The shear breaking strength is 200N / inch 2 If the shear breaking strength is 500 N / inch or more, the strength of the foam substrate is sufficiently high, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. 2 If the shear breaking strength is less than 220 N / inch, the flexibility of the foam base material can be prevented from decreasing too much, thereby reducing display unevenness of a display device, and the foam base material can be easily torn when peeling the double-sided pressure-sensitive adhesive tape from an adherend. 2 , the preferred upper limit is 470N / inch 2 and a more preferable lower limit is 240N / inch 2 , and a more preferable upper limit is 450N / inch 2 and a more preferable lower limit is 270 N / inch 2 , and a more preferable upper limit is 415N / inch 2 It is.

[0038] The shear breaking strength can be measured by the following method. FIG. 1 shows a schematic diagram of a method for measuring shear breaking strength. First, a test piece 18 of double-sided adhesive tape with a size of 25 mm×25 mm and two SUS plates 19 with a size of 125 mm×50 mm and a thickness of 2 mm are laminated as shown in FIG. 1. This laminate is pressed with a weight of 5 kg for 10 seconds, and then left to stand for 24 hours to prepare a test sample in which two SUS plates 19 are bonded together via the test piece 18. After fixing one SUS plate 19 of this test sample, the upper one of the other SUS plate 19 is pulled at 23° C. in a direction perpendicular to the lamination direction of the SUS plates (in the direction of the arrow in the figure) at 12.7 mm / min, and the force (breaking strength) applied to the test piece 18 when the test piece 18 breaks is measured. Note that the breakage of the test piece 18 means that the foam base material breaks between layers. The shear breaking strength of the foam base material can be adjusted by changing the type and content of the polyisocyanate and polyol in the urethane resin composition. Even when the raw materials are the same, it can be adjusted by setting the bubble volume fraction, the average and standard deviation of the bubble major axis distribution, etc. within appropriate ranges.

[0039] The 25% compressive strength of the foam substrate is not particularly limited, but the preferred lower limit is 0.015 MPa, and the preferred upper limit is 0.08 MPa. If the 25% compressive strength is 0.015 MPa or more, the strength of the foam substrate is sufficiently high, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. If the 25% compressive strength is 0.08 MPa or less, the flexibility of the foam substrate can be prevented from decreasing too much, so that the double-sided pressure-sensitive adhesive tape can be well pressure-bonded, the display unevenness of the display device can be reduced, and the foam substrate can be easily torn when the double-sided pressure-sensitive adhesive tape is peeled off from the adherend. The more preferred lower limit of the 25% compressive strength is 0.02 MPa, the more preferred upper limit is 0.07 MPa, the even more preferred lower limit is 0.025 MPa, the even more preferred upper limit is 0.065 MPa, the even more preferred lower limit is 0.03 MPa, and the even more preferred upper limit is 0.06 MPa. The 25% compressive strength can be determined by measuring in accordance with JIS K 6254:2010. The 25% compressive strength of the foam base material can be adjusted by changing the type and content of the polyisocyanate and polyol in the urethane resin composition. Even when the raw materials are the same, it can be adjusted by setting the bubble volume fraction, the average and standard deviation of the bubble major axis distribution, etc. within appropriate ranges.

[0040] The glass transition point of the foam substrate is not particularly limited, but the preferred lower limit is -30°C, and the preferred upper limit is 30°C. If the glass transition point of the foam substrate is -30°C or higher, the foam substrate exhibits good low resilience and can relieve stress. If the glass transition point of the foam substrate is 30°C or lower, the foam substrate can have appropriate flexibility, and the foam becomes easily stretchable, resulting in high strength and flexibility. The more preferred lower limit of the glass transition point of the foam substrate is -25°C, and the more preferred upper limit is 20°C. The glass transition point can be determined using a viscoelasticity measuring device (for example, Rheometrics Dynamic Analyze RDA-700 manufactured by Rheometrics) under conditions of a measurement temperature of -30 to 100°C, a temperature rise rate of 3°C / min, and a frequency of 1 Hz.

[0041] The thickness of the foam substrate is not particularly limited, but the preferred lower limit is 100 μm, and the preferred upper limit is 1000 μm. If the thickness of the foam substrate is 100 μm or more, the foam substrate can have appropriate flexibility. If the thickness of the foam substrate is 1000 μm or less, the variation in the size of the bubbles can be suppressed, and the foam substrate can be prevented from being stretched and broken due to impact caused by dropping during transportation. The more preferred lower limit of the thickness of the foam substrate is 150 μm, the more preferred upper limit is 950 μm, the even more preferred lower limit is 300 μm, the even more preferred upper limit is 750 μm, the even more preferred lower limit is 450 μm, and the even more preferred upper limit is 700 μm. The thickness of the foam substrate can be measured using a dial thickness meter (for example, "ABS Digimatic Indicator" manufactured by Mitutoyo Corporation).

[0042] The double-sided pressure-sensitive adhesive tape of the present invention may further include a resin sheet on at least one side of the foam substrate. By using the resin sheet, it is possible to prevent the foam substrate from stretching and breaking during handling, and it is possible to impart reworkability to the double-sided pressure-sensitive adhesive tape. The resin sheet may be laminated on one side or both sides of the foam substrate. The resin constituting the resin sheet is not particularly limited, and examples thereof include polyester resins such as polyethylene terephthalate, acrylic resins, polyethylene resins, polypropylene resins, polyvinyl chloride, epoxy resins, silicone resins, phenol resins, polyimide, polyester, polycarbonate, etc. Among these, acrylic resins, polyethylene resins, polypropylene resins, and polyester resins are preferred because of their excellent flexibility. Among polyester resins, polyethylene terephthalate is preferred.

[0043] The resin constituting the resin sheet may be a thermoplastic resin. The thermoplastic resin is not particularly limited, and examples thereof include styrene-based (co)polymers, olefin-based (co)polymers, vinyl chloride-based (co)polymers, polyether ester-based triblock (co)polymers, polyester-based (co)polymers, urethane-based (co)polymers, amide-based (co)polymers, and acrylic-based (co)polymers. Among them, the thermoplastic resin is preferably an acrylic (co)polymer, a styrene-based (co)polymer, or an olefin-based (co)polymer, from the viewpoint of being able to exhibit strength, elongation, flexibility, and self-adhesiveness as an elastic body, and being able to further improve the adhesion between the resin sheet and the foam substrate while exhibiting excellent reworkability. Furthermore, it is more preferable that the thermoplastic resin is an acrylic (co)polymer or a styrene-based (co)polymer, and even more preferable that the thermoplastic resin is a styrene-based (co)polymer.

[0044] When the resin constituting the resin sheet is a thermoplastic resin, the resin sheet preferably has a tensile modulus of elasticity of 200 MPa or less. By using a flexible resin having a tensile modulus of elasticity of 200 MPa or less, the flexibility of the double-sided pressure-sensitive adhesive tape as a whole is ensured, making it easier to wind the double-sided pressure-sensitive adhesive tape into a roll, and significantly improving the handleability. The tensile modulus can be measured by a method conforming to JIS K 7161. Specifically, for example, a resin sheet is punched into a dumbbell shape using a punching blade such as "Tensile No. 1 Dumbbell Shape" manufactured by Kobunshi Keiki Co., Ltd. to prepare a test piece. The tensile modulus of the obtained test piece is measured at a tensile speed of 100 mm / min using, for example, "Autograph AGS-X" manufactured by Shimadzu Corporation. The tensile modulus is calculated from the slope of the tensile strength between 1 and 3% strain.

[0045] When the resin sheets are laminated on both sides of the foam substrate, the resin constituting at least one of the resin sheets is preferably a thermoplastic resin. That is, the double-sided pressure-sensitive adhesive tape of the present invention preferably has a resin sheet composed of a thermoplastic resin. The double-sided adhesive tape of the present invention has a first resin sheet laminated on a first surface of the foam substrate and a second resin sheet laminated on a second surface of the foam substrate, and it is preferable that at least one selected from the group consisting of the first resin sheet and the second resin sheet is a resin sheet composed of a thermoplastic resin.

[0046] The thickness of the resin sheet is not particularly limited, but the preferred lower limit is 10 μm, and the preferred upper limit is 100 μm. If the thickness of the resin sheet is 10 μm or more, the resin sheet is less likely to break when pulled. If the thickness of the resin sheet is 100 μm or less, the decrease in the conformability to the adherend can be suppressed. The more preferred lower limit of the thickness of the resin sheet is 15 μm, the more preferred upper limit is 80 μm, the even more preferred lower limit is 20 μm, the even more preferred upper limit is 60 μm, the even more preferred lower limit is 25 μm, and the even more preferred upper limit is 50 μm.

[0047] The resin sheet may be colored. By coloring the resin sheet, it is possible to impart light-shielding properties to the double-sided pressure-sensitive adhesive tape. The method for coloring the resin sheet is not particularly limited, and examples thereof include a method of kneading particles of carbon black, titanium oxide, or the like, or fine air bubbles into the resin constituting the resin sheet, and a method of applying ink to the surface of the resin sheet.

[0048] The pressure-sensitive adhesive layers laminated on both sides of the foam substrate may have the same composition or different compositions. The pressure-sensitive adhesive layer is not particularly limited, and examples thereof include pressure-sensitive adhesive layers made of acrylic pressure-sensitive adhesives, rubber-based pressure-sensitive adhesives, urethane pressure-sensitive adhesives, silicone-based pressure-sensitive adhesives, etc. Among these, a pressure-sensitive adhesive layer made of an acrylic pressure-sensitive adhesive containing an acrylic copolymer and a tackifier is preferred, since the adhesive strength can be easily adjusted, it is relatively stable against light, heat, moisture, etc., and it can be applied to various adherends.

[0049] The acrylic copolymer is obtained by copolymerizing the monomer mixture. To obtain the acrylic copolymer by copolymerizing the monomer mixture, the monomer mixture may be subjected to a radical reaction in the presence of a polymerization initiator. As a method for radically reacting the monomer mixture, that is, a polymerization method, a conventionally known method is used, and examples of the method include solution polymerization (boiling point polymerization or constant temperature polymerization), emulsion polymerization, suspension polymerization, and bulk polymerization. Examples of the reaction method when the monomer mixture is radically reacted include living radical polymerization and free radical polymerization.

[0050] The ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the acrylic copolymer (molecular weight distribution, Mw / Mn) is not particularly limited, but a preferred lower limit is 1.05, and a preferred upper limit is 5.0. If the molecular weight distribution (Mw / Mn) is within the above range, the content of low molecular weight components and the like is reduced, so that the cohesive force of the pressure-sensitive adhesive layer increases and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. A more preferred upper limit of the molecular weight distribution (Mw / Mn) is 3.0, an even more preferred upper limit is 2.5, and a particularly preferred upper limit is 2.3. To adjust the molecular weight distribution (Mw / Mn) to the above range, the polymerization conditions such as the polymerization initiator and polymerization temperature may be adjusted. The number average molecular weight (Mn) and weight average molecular weight (Mw) are molecular weights calculated based on standard polystyrene standards by gel permeation chromatography (GPC). For GPC, for example, 2690 Separations Model (Waters) can be used. Also, a GPC device (for example, Tosoh Corporation, product name "HLC-8220", column: TSKgelSurper HZM-N (4 columns)) can be used, and tetrahydrofuran can be used as a solvent. For example, 40°C and a flow rate of 0.5 mL / min can be used as measurement conditions.

[0051] When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or less, the acrylic copolymer preferably contains a constituent unit derived from 2-ethylhexyl acrylate. When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or less, the content of the structural unit derived from the 2-ethylhexyl acrylate is not particularly limited, but the preferred lower limit is 80% by weight, and the preferred upper limit is 98% by weight. When the content of the structural unit is 80% by weight or more, the glass transition point of the acrylic copolymer is lowered, the wettability of the pressure-sensitive adhesive layer to the adherend is increased, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. When the content of the structural unit is 98% by weight or less, the cohesive force of the pressure-sensitive adhesive layer is increased, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. The more preferred lower limit of the content of the structural unit is 90% by weight, and the more preferred upper limit is 97% by weight.

[0052] When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or more, the acrylic copolymer preferably contains a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 4 or less carbon atoms. When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or more, the (meth)acrylic acid alkyl ester having an alkyl group having 4 or less carbon atoms is not particularly limited. Examples of the (meth)acrylic acid alkyl ester having an alkyl group having 4 or less carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, and n-butyl (meth)acrylate. Among them, ethyl (meth)acrylate and n-butyl (meth)acrylate are preferred, and these acrylates are more preferred. These (meth)acrylic acid alkyl esters having an alkyl group having 4 or less carbon atoms may be used alone or in combination of two or more.

[0053] When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or more, the content of the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group having 4 or less carbon atoms is not particularly limited, but the preferred lower limit is 40% by weight, and the preferred upper limit is 80% by weight. When the content of the structural unit is 40% by weight or more, the cohesive force of the pressure-sensitive adhesive layer increases, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves. When the content of the structural unit is 80% by weight or less, the wettability of the pressure-sensitive adhesive layer with respect to the adherend can be prevented from decreasing too much, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves.

[0054] Even when the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or more, the acrylic copolymer preferably contains a constituent unit derived from 2-ethylhexyl acrylate. When the molecular weight distribution (Mw / Mn) of the acrylic copolymer is 2.5 or more, the content of the structural unit derived from the 2-ethylhexyl acrylate is not particularly limited, but the preferred lower limit is 10% by weight, and the preferred upper limit is 40% by weight. When the content of the structural unit is 10% by weight or more, the cohesive strength of the pressure-sensitive adhesive layer increases, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves. When the content of the structural unit is 40% by weight or less, the cohesive strength of the pressure-sensitive adhesive layer can be prevented from decreasing too much, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves.

[0055] The acrylic copolymer may contain, as necessary, a structural unit derived from another copolymerizable polymerizable monomer other than the structural unit derived from 2-ethylhexyl acrylate and the structural unit derived from the (meth)acrylic acid alkyl ester having an alkyl group having 4 or less carbon atoms. Examples of the other copolymerizable monomer include (meth)acrylic acid alkyl esters having an alkyl group having 13 to 18 carbon atoms, and functional monomers. Examples of the (meth)acrylic acid alkyl ester having an alkyl group having 13 to 18 carbon atoms include tridecyl methacrylate, stearyl (meth)acrylate, etc. Examples of the functional monomer include hydroxyalkyl (meth)acrylate, glycerin dimethacrylate, glycidyl (meth)acrylate, 2-methacryloyloxyethyl isocyanate, (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, fumaric acid, etc. These copolymerizable other polymerizable monomers may be used alone or in combination of two or more.Among them, functional monomers having polar functional groups such as hydroxyl groups and carboxyl groups are preferred, and functional monomers having hydroxyl groups are more preferred, since forming a crosslinked structure with a crosslinking agent makes it easier to adjust the gel fraction of the pressure-sensitive adhesive layer.That is, the acrylic copolymer preferably contains a hydroxyl group.

[0056] The weight average molecular weight (Mw) of the acrylic copolymer has a preferred lower limit of 300,000 and a preferred upper limit of 2,000,000. If the weight average molecular weight is 300,000 or more, the pressure-sensitive adhesive layer has a moderate hardness, sufficient cohesive force, and high adhesive strength. If the weight average molecular weight is 2,000,000 or less, the adhesive strength of the pressure-sensitive adhesive layer is sufficient. A more preferred lower limit of the weight average molecular weight is 500,000 and a more preferred upper limit is 1,400,000. To adjust the weight average molecular weight to the above range, polymerization conditions such as the polymerization initiator and polymerization temperature may be adjusted.

[0057] Examples of the polymerization initiator include organic peroxides and azo compounds. Examples of the organic peroxides include 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxy-3,5,5-trimethylhexanoate, and t-butylperoxylaurate. The azo compound is not particularly limited as long as it is generally used in radical polymerization. Examples of the azo compound include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, 4,4' -Azobis(4-cyanovaleric acid), dimethyl-2,2'-azobis(2-methylpropionate), dimethyl-1,1'-azobis(1-cyclohexanecarboxylate), 2,2'-azobis{2-methyl-N-[1,1'-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2 '-Azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane} dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, 2,2'-azobis(2,4,4-trimethylpentane), and the like. The polymerization initiator that initiates living radical polymerization is not particularly limited, but an organotellurium polymerization initiator is preferred. These polymerization initiators may be used alone or in combination of two or more kinds.

[0058] When the monomer mixture is subjected to a radical reaction, a dispersion stabilizer may be used. Examples of the dispersion stabilizer include polyvinylpyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, poly(meth)acrylic acid, poly(meth)acrylic acid ester, and polyethylene glycol.

[0059] When a polymerization solvent is used in the radical reaction of the monomer mixture, the polymerization solvent is not particularly limited. As the polymerization solvent, for example, a non-polar solvent such as hexane, cyclohexane, octane, toluene, or xylene can be used. In addition, as the polymerization solvent, for example, a highly polar solvent such as water, methanol, ethanol, propanol, butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, or N,N-dimethylformamide can be used. These polymerization solvents may be used alone or in combination of two or more. The polymerization temperature is preferably 0 to 110° C. from the viewpoint of polymerization rate.

[0060] Examples of the tackifier include rosin resins, rosin ester resins, hydrogenated rosin resins, terpene resins, terpene phenol resins, coumarone-indene resins, alicyclic saturated hydrocarbon resins, C5 petroleum resins, C9 petroleum resins, and C5-C9 copolymer petroleum resins. These tackifiers may be used alone or in combination of two or more. Among these, rosin resins or terpene resins are preferred, and hydroxyl-containing rosin resins or hydroxyl-containing terpene resins are more preferred.

[0061] The tackifier has a softening temperature of preferably 70°C or lower and 170°C or upper. If the softening temperature is 70°C or higher, the pressure-sensitive adhesive layer can be prevented from becoming too soft, which can prevent the drop impact resistance of the double-sided pressure-sensitive adhesive tape from decreasing. If the softening temperature is 170°C or lower, the wettability of the pressure-sensitive adhesive layer to the adherend is increased, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape is improved. The more preferred lower limit of the softening temperature is 120°C. The softening temperature is measured by the ring and ball method according to JIS K2207.

[0062] The tackifier has a hydroxyl value of preferably 25 at the lower limit and 160 at the upper limit. When the hydroxyl value is within the above range, the adhesive layer has high wettability with respect to the adherend, and the drop impact resistance of the double-sided adhesive tape is improved. The hydroxyl value is more preferably 30 at the lower limit and 150 at the upper limit. The hydroxyl value can be measured according to JIS K1557 (phthalic anhydride method).

[0063] The content of the tackifier is not particularly limited, but the preferred lower limit is 10 parts by weight and the preferred upper limit is 60 parts by weight relative to 100 parts by weight of the acrylic copolymer. If the content of the tackifier is 10 parts by weight or more, the adhesive strength of the adhesive layer is high. If the content of the tackifier is 60 parts by weight or less, the adhesive layer can be prevented from becoming too hard and losing its adhesive strength.

[0064] The pressure-sensitive adhesive layer preferably has a crosslinked structure formed between the main chains of the resins (e.g., the acrylic copolymer, the tackifier, etc.) constituting the pressure-sensitive adhesive layer by adding a crosslinking agent. By adjusting the type and amount of the crosslinking agent, the gel fraction of the pressure-sensitive adhesive layer can be easily adjusted. The crosslinking agent is not particularly limited, and examples thereof include isocyanate-based crosslinking agents, aziridine-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-type crosslinking agents, etc. Among these, isocyanate-based crosslinking agents are preferred. The amount of the crosslinking agent added is preferably 0.01 part by weight at its lower limit and 10 parts by weight at its upper limit, more preferably 0.1 part by weight at its lower limit and 3 parts by weight at its upper limit, per 100 parts by weight of the acrylic copolymer.

[0065] The pressure-sensitive adhesive layer may contain a silane coupling agent for the purpose of improving adhesive strength. The silane coupling agent is not particularly limited, and examples thereof include epoxy silanes, acrylic silanes, methacrylic silanes, amino silanes, and isocyanate silanes.

[0066] The pressure-sensitive adhesive layer may contain a coloring material for the purpose of imparting light-shielding properties. The coloring material is not particularly limited, and examples thereof include carbon black, aniline black, titanium oxide, etc. Among these, carbon black is preferred because it is relatively inexpensive and chemically stable.

[0067] The gel fraction of the pressure-sensitive adhesive layer is not particularly limited, but the preferred lower limit is 1% by weight, and the preferred upper limit is 90% by weight. If the gel fraction is 1% by weight or more, the cohesive force of the pressure-sensitive adhesive layer increases, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves. If the gel fraction is 90% by weight or less, the wettability of the pressure-sensitive adhesive layer to the adherend can be prevented from decreasing too much, and the drop impact resistance of the double-sided pressure-sensitive adhesive tape improves. The more preferred lower limit of the gel fraction is 20% by weight, and the more preferred upper limit is 70% by weight, and the even more preferred lower limit is 30% by weight, and the even more preferred upper limit is 50% by weight. The gel fraction of the pressure-sensitive adhesive layer can be measured by the following method. The double-sided adhesive tape is cut into a flat rectangular shape of 50 mm x 100 mm to prepare a test piece. The test piece is immersed in ethyl acetate at 23°C for 24 hours, then removed from the ethyl acetate and dried at 110°C for 1 hour. The weight of the test piece after drying is measured, and the gel fraction is calculated using the following formula (5). Note that no release film is laminated on the test piece to protect the adhesive layer. Gel fraction (weight%) = 100 × (W2-W0) / (W1-W0) (5) (W0: weight of substrate, W1: weight of test piece before immersion, W2: weight of test piece after immersion and drying)

[0068] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but the preferred lower limit of the thickness of the pressure-sensitive adhesive layer on one side is 20 μm, and the preferred upper limit is 100 μm. If the thickness of the pressure-sensitive adhesive layer is 20 μm or more, the adhesive strength of the pressure-sensitive adhesive layer is sufficient. If the thickness of the pressure-sensitive adhesive layer is 100 μm or less, the stress relaxation property of the foam substrate can sufficiently contribute to the stress relaxation property of the double-sided pressure-sensitive adhesive tape as a whole. The more preferred lower limit of the thickness of the pressure-sensitive adhesive layer is 25 μm, and the more preferred upper limit is 80 μm, and the even more preferred lower limit is 30 μm, and the even more preferred upper limit is 70 μm, and the even more preferred lower limit is 35 μm, and the even more preferred upper limit is 65 μm. The thickness of the pressure-sensitive adhesive layer can be measured using a dial thickness meter (for example, "ABS Digimatic Indicator" manufactured by Mitutoyo Corporation).

[0069] The thickness of the double-sided adhesive tape of the present invention is not particularly limited, but the preferred lower limit is 100 μm, and the preferred upper limit is 1200 μm. If the thickness is 100 μm or more, the adhesive strength of the double-sided adhesive tape is sufficient, and the stress relaxation property is also sufficient. If the thickness is 1200 μm or less, sufficient adhesion and fixation by the double-sided adhesive tape can be realized. The more preferred lower limit of the thickness is 250 μm, the more preferred upper limit is 900 μm, the even more preferred lower limit is 350 μm, the even more preferred upper limit is 700 μm, the even more preferred lower limit is 400 μm, and the even more preferred upper limit is 650 μm.

[0070] The configuration of the double-sided pressure-sensitive adhesive tape of the present invention is not particularly limited, and the pressure-sensitive adhesive layer may be laminated on the surface of the foam substrate, or the resin sheet may be laminated between the foam substrate and the pressure-sensitive adhesive layer.

[0071] The double-sided pressure-sensitive adhesive tape of the present invention can be produced, for example, by the following method. First, a solvent is added to the acrylic copolymer and, if necessary, a tackifier and a crosslinking agent to prepare a solution of adhesive A, which is then applied to the surface of a foam substrate and the solvent in the solution is completely dried to form adhesive layer A. Next, a release film is placed on top of the formed adhesive layer A with its release-treated surface facing the adhesive layer A. Next, a release film other than the above release film is prepared, and a solution of adhesive B is applied to the release-treated surface of this release film, and the solvent in the solution is completely dried and removed to produce a laminated film in which adhesive layer B is formed on the surface of the release film. The obtained laminated film is superimposed on the back surface of the foam substrate on which adhesive layer A is formed, with adhesive layer B facing the back surface of the foam substrate to produce a laminate. Then, the laminate is pressed with a rubber roller or the like. This makes it possible to obtain a double-sided adhesive tape having adhesive layers on both sides of the foam substrate and the surface of the adhesive layer covered with a release film.

[0072] Alternatively, two sets of laminate films may be prepared in a similar manner, and these laminate films may be superimposed on both sides of a foam substrate with the pressure-sensitive adhesive layers of the laminate films facing the foam substrate to prepare a laminate, which may then be pressed with a rubber roller, etc. This makes it possible to obtain a double-sided pressure-sensitive adhesive tape having pressure-sensitive adhesive layers on both sides of the foam substrate, and in which the surfaces of the pressure-sensitive adhesive layers are covered with release films.

[0073] The double-sided pressure-sensitive adhesive tape of the present invention can be used for, for example, fixing components in electronic devices. The electronic devices are not particularly limited, and examples thereof include televisions, monitors, portable electronic devices, and in-vehicle electronic devices. In particular, the double-sided adhesive tape of the present invention is preferably used for fixing components in display devices such as televisions and monitors, particularly in relatively large display devices, and is specifically used, for example, for fixing the cover panel on the surface of the display device to the housing. The double-sided adhesive tape of the present invention has excellent drop impact resistance and can reduce display unevenness of the display device, so it is preferably used even when components are fixed with a narrow double-sided adhesive tape in a relatively large display device. The double-sided adhesive tape of the present invention may be narrow, and the width is not particularly limited, but the preferred lower limit is 1000 μm, the preferred upper limit is 10000 μm, the more preferred lower limit is 1500 μm, and the more preferred upper limit is 5000 μm. The shape of the double-sided adhesive tape of the present invention in these applications is not particularly limited, but examples thereof include rectangular, frame-shaped, circular, elliptical, and donut-shaped shapes. The double-sided pressure-sensitive adhesive tape of the present invention may also be used for vehicle interiors, and the interior and exterior of home appliances (for example, TVs, air conditioners, refrigerators, etc.). Effect of the Invention

[0074] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive tape that has excellent resistance to drop impact, can reduce display unevenness on a display device, and has a foam base material that can be easily torn when peeled off from an adherend. [Brief description of the drawings]

[0075] [Figure 1] FIG. 2 is a schematic diagram showing a method for measuring shear breaking strength. [Diagram 2] FIG. 2 is a schematic diagram showing an interlayer tear test of a double-sided pressure-sensitive adhesive tape. [Diagram 3] FIG. 2 is a schematic diagram showing a sample for a tumble test of a double-sided pressure-sensitive adhesive tape. [Figure 4] FIG. 2 shows a schematic diagram illustrating a surface waviness test of a double-sided adhesive tape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0077] (Production of Polyurethane Foam 1-1 (PU1-1)) As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 10 parts by weight of 1,5-pentanediol were used. To a total of 100 parts by weight of polyol, 0.7 parts by weight of an amine catalyst (DABCO LV33, manufactured by Sankyo Air Products Co., Ltd.) and 1 part by weight of a foam stabilizer (SZ5740M, manufactured by Toray Dow Corning Co., Ltd.) were added and stirred. Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 85. Then, 0.2 g / cm 3 The mixture was mixed with nitrogen gas and stirred until a solution containing fine bubbles was obtained. The solution was applied to a specified thickness on a 50 μm-thick PET separator (Nippa, V-2) using an applicator, and the foam raw materials were reacted to obtain a polyurethane foam. The shear breaking strength, 25% compression strength, and thickness of the polyurethane foam were measured. The polyurethane foam was cut to obtain a measurement sample, and the center of the sample was imaged using an X-ray CT scanner (Yamato Scientific Co., Ltd., "TDM1000H-II (2K)", resolution 1.5 μm / 1 pixel) to obtain a rectangular 3D image of 1.5 mm in length, 1.2 mm in width, and 0.3 mm in height. The image was subjected to noise removal and binarization using image analysis software (FEI Co., Ltd., "Avizo9.2.0") to determine the bubble volume fraction, the average and standard deviation of the bubble major axis distribution, the open cell ratio, the bubble aspect ratio, and the bubble flattening ratio.

[0078] (Production of Polyurethane Foam 1-2 (PU1-2)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 5 parts by weight of 1,5-pentanediol, and 5 parts by weight of 1,6-hexamethylenediol were used. [2] Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was adjusted to have an isocyanate index of 85 and added.

[0079] (Production of Polyurethane Foam 1-3 (PU1-3)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 5 parts by weight of 1,5-pentanediol, and 5 parts by weight of neopentyl glycol were used.

[0080] (Production of polyurethane foam 2 (PU2)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As polyols, 85 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 3 parts by weight of 1,6-hexamethylene diol, 3 parts by weight of neopentyl glycol, and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 90.

[0081] (Production of Polyurethane Foam 3-1 (PU3-1)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 91 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 100. [3] The amount of nitrogen gas mixed in was adjusted, and the thickness of the solution containing fine bubbles was changed (thinnered) when it was applied to a 50 μm thick PET separator (Nippa, V-2).

[0082] (Production of Polyurethane Foam 3-2 (PU3-2)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 91 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 100.

[0083] (Production of Polyurethane Foam 3-3 (PU3-3)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 91 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 100. [3] The amount of nitrogen gas mixed in was adjusted, and the thickness at which the solution containing fine bubbles was applied onto a 50 μm-thick PET separator (Nippa, V-2) was changed (made thicker).

[0084] (Production of Polyurethane Foam 4 (PU4)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 5 parts by weight of 1,5-pentanediol, and 5 parts by weight of 1,6-hexamethylenediol were used. [2] Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 75.

[0085] (Production of Polyurethane Foam 5 (PU5)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 10 parts by weight of 1,6-hexamethylene diol were used. [2] Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 95.

[0086] (Production of Polyurethane Foam 6 (PU6)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 90 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 10 parts by weight of 1,5-pentanediol were used. [2] Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was adjusted to have an isocyanate index of 70 and added.

[0087] (Production of Polyurethane Foam 7 (PU7)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As the polyol, 91 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was adjusted to have an isocyanate index of 110 and added.

[0088] (Production of Polyurethane Foam 8 (PU8)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 3-1 (PU3-1), except for the following points. [1] As the polyol, 91 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000) and 9 parts by weight of ε-caprolactone were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was adjusted to have an isocyanate index of 85 and added.

[0089] (Production of Polyurethane Foam 9 (PU9)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 8 (PU8), except for the following points. [1] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was adjusted to have an isocyanate index of 90 and added.

[0090] (Production of Polyurethane Foam 10 (PU10)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] Polyisocyanate (dinuclear monomeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 70. [2] The amount of nitrogen gas mixed in was adjusted, and the thickness at which the solution containing fine bubbles was applied onto a 50 μm-thick PET separator (Nippa, V-2) was changed (made thicker).

[0091] (Production of Polyurethane Foam 11 (PU11)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As polyols, 30 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 60 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 3100), and 10 parts by weight of 1,5-pentanediol were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 65. [3] The amount of nitrogen gas mixed in was adjusted, and the thickness at which the solution containing fine bubbles was applied onto a 50 μm-thick PET separator (Nippa, V-2) was changed (made thicker).

[0092] (Production of polyurethane foam 12 (PU12)) A polyurethane foam was obtained in the same manner as in the production of polyurethane foam 1-1 (PU1-1), except for the following points. [1] As polyols, 20 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 1000), 70 parts by weight of polypropylene glycol (PPG) (weight average molecular weight 3100), and 10 parts by weight of 1,5-pentanediol were used. [2] Polyisocyanate (Polymeric MDI, manufactured by Tosoh Corporation) was added after adjusting the isocyanate index to 65. [3] The amount of nitrogen gas mixed in was adjusted, and the thickness at which the solution containing fine bubbles was applied onto a 50 μm-thick PET separator (Nippa, V-2) was changed (made thicker).

[0093] (Polyethylene foam 1 (PE1)) As the polyethylene foam, XLIM#15003 (manufactured by Sekisui Chemical Co., Ltd.) was used.

[0094] (Production of Adhesive I (Radical Polymerization)) 52 parts by weight of ethyl acetate was put into a reactor equipped with a thermometer, a stirrer, and a cooling tube, and after replacing with nitrogen, the reactor was heated to start reflux. 30 minutes after the ethyl acetate boiled, 0.08 parts by weight of azobisisobutyronitrile was put in as a polymerization initiator. A monomer mixture (60 parts by weight of butyl acrylate (BA), 36.9 parts by weight of 2-ethylhexyl acrylate (2EHA), 3 parts by weight of acrylic acid (AAc), and 0.1 parts by weight of 2-hydroxyethyl acrylate (2HEA)) was added dropwise evenly and gradually over 1 hour and 30 minutes to react. 30 minutes after the end of the dropwise addition, 0.1 parts by weight of azobisisobutyronitrile was added, and the polymerization reaction was continued for another 5 hours, and ethyl acetate was added to the reactor to dilute it while cooling, thereby obtaining an acrylic copolymer-containing solution.

[0095] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the obtained acrylic copolymer were obtained. Specifically, the obtained acrylic copolymer-containing solution was diluted 50 times with tetrahydrofuran (THF), and the obtained diluted solution was filtered with a filter (material: polytetrafluoroethylene, pore size: 0.2 μm). The obtained filtrate was supplied to a gel permeation chromatograph (Waters, 2690 Separations Model) and GPC measurement was performed under conditions of a sample flow rate of 1 milliliter / min and a column temperature of 40°C, and the polystyrene-equivalent molecular weight of the acrylic copolymer was measured to obtain the weight average molecular weight and molecular weight distribution (Mw / Mn). The weight average molecular weight was 1 million, and the molecular weight distribution (Mw / Mn) was 2.6. A GPC KF-806L (Showa Denko) was used as the column, and a differential refractometer was used as the detector.

[0096] Ethyl acetate was added to 100 parts by weight of the nonvolatile content of the obtained acrylic copolymer-containing solution and stirred, and 5 parts by weight of a crosslinking agent (isocyanate-based crosslinking agent, Coronate L-55E, manufactured by Tosoh Corporation) and a total of 30 parts by weight of a tackifier were added and stirred to obtain an adhesive I with a nonvolatile content of 30% by weight. As the tackifier, 10 parts by weight of a hydrogenated rosin-based resin (softening point 100°C, hydroxyl value 40 mgKOH / g), 10 parts by weight of a rosin ester-based resin (softening point 150°C, hydroxyl value 40 mgKOH / g), and 10 parts by weight of a terpene phenol-based resin (softening point 150°C, hydroxyl value 40 mgKOH / g) were used.

[0097] (Examples 1 to 12, Comparative Examples 1 to 5) The adhesive I was applied to the support layer 1 (resin sheet) and dried at 100°C for 5 minutes to form an adhesive layer 1 with a thickness of 20 μm. One side of the foam substrate was pressed against the adhesive layer 1 to produce a laminate in which the support layer 1 and the foam substrate were laminated via the adhesive layer 1. As the support layer 1 (resin sheet), polyethylene terephthalate (PET) (X30, manufactured by Toray Industries, Inc., thickness 50 μm) was used. Next, the support layer 2 (resin sheet) was heat-sealed to the other side of the foam substrate to produce a laminate in which the support layer 1, adhesive layer 1, foam substrate, and support layer 2 were laminated in this order. As the support layer 2 (resin sheet), a sheet made of an acrylic resin (LA2250, manufactured by Kuraray Co., Ltd., thickness 50 μm) or a urethane block copolymer (TPU) (1198ATR, manufactured by BASF, thickness 20 μm) was used. Next, a release paper having a thickness of 150 μm was prepared, and the adhesive I was applied to the release-treated surface of the release paper, and dried at 100° C. for 5 minutes to form an adhesive layer 2 having a thickness of 50 μm, 55 μm, or 60 μm. This adhesive layer 2 was attached to the surface of the support layer 1 (resin sheet) laminated on the foam substrate. Next, in the same manner, an adhesive layer 3 having the same configuration as the adhesive layer 2 was attached to the surface of the support layer 2 (resin sheet) opposite the foam substrate. Thereafter, the adhesive layer was cured by heating at 40° C. for 48 hours. As a result, a double-sided adhesive tape covered with release paper was obtained. The tensile modulus of elasticity of the support layer 2 (resin sheet) was 10 MPa and 108 MPa, respectively.

[0098] The obtained double-sided pressure-sensitive adhesive tape was cut into a flat rectangular shape of 50 mm × 100 mm to prepare a test piece, which was then immersed in ethyl acetate at 23° C. for 24 hours, removed from the ethyl acetate, and dried for 1 hour at 110° C. The weight of the test piece after drying was measured, and the gel fraction of the pressure-sensitive adhesive layer was calculated using the following formula (5), which was 42% by weight. Gel fraction (weight%) = 100 × (W2-W0) / (W1-W0) (5) (W0: weight of substrate, W1: weight of test piece before immersion, W2: weight of test piece after immersion and drying)

[0099] <Evaluation> The double-sided pressure-sensitive adhesive tapes obtained in the Examples and Comparative Examples were evaluated as follows, and the results are shown in Tables 1 and 2.

[0100] (1) Rework (interlaminar tear test) FIG. 2 shows a schematic diagram of an interlaminar tear test of a double-sided adhesive tape. FIG. 2(a) is a front view, and FIG. 2(b) is a side view. A test piece 2 of double-sided adhesive tape with a size of 50 mm×5 mm and two PC plates 1 with a size of 100 mm×20 mm and a thickness of 2 mm were laminated as shown in FIG. 2. This laminate was pressed with a weight of 5 kg for 10 seconds, and then left for 24 hours to prepare a tear test sample in which two PC plates 1 were bonded together via the test piece 2. After fixing one of the PC plates of this tear test sample, a stainless steel wire 3 (0.3φ, TRUSCO "TYWS-03") was hooked from under the test piece 2 and pulled in the direction of the arrow in FIG. 2 at 300 mm / min. The test force when the wire 3 tears the base material layers of the test piece 2 apart was measured. A test force of less than 10 N / 5 mm was indicated as ⊚, a test force of 10 N / 5 mm or more but less than 15 N / 5 mm was indicated as ◯, and a test force of 15 N / 5 mm or more was indicated as ×.

[0101] (2) Drop impact resistance (tumble test) FIG. 3 shows a schematic diagram of a double-sided adhesive tape tumble test sample. A frame-shaped test piece 6 of the double-sided adhesive tape, measuring 23 mm long x 13.3 mm short, and 3.2 mm wide, was sandwiched between a PMMA plate 5 measuring 55 mm x 65 mm, 10 mm thick, and 42 g in weight, and a SUS plate 4 measuring 70 mm x 130 mm, 2 mm thick, and 137 g in weight, and laminated as shown in FIG. 3. This laminate was pressed with a weight of 5 kg for 10 seconds, and then left for 24 hours to prepare a tumble test sample in which the PMMA plate 5 and the SUS plate 4 were bonded together via the test piece 6. The tumble test sample was placed in a tumble tester (TDR-1000A-SC01, manufactured by Shin-Ei Electronic Measuring Instruments Co., Ltd.) and repeatedly subjected to drop impacts from various angles at a frequency of 10 drops / min. The number of drops was measured until the double-sided adhesive tape broke and the tumble test sample was separated. A drop of 30 or more times was indicated by ◎, a drop of 10 to less than 30 times was indicated by ◯, and a drop of less than 10 times was indicated by ×.

[0102] (3) Display unevenness (surface waviness test) FIG. 4 shows a schematic diagram of a surface waviness test of a double-sided adhesive tape. FIG. 4(a) is a top view, and FIG. 4(b) is a cross-sectional view. A single-sided black light-shielding tape 8 having a width of 15 mm and a thickness of 50 μm was laminated at intervals of 15 mm on a glass plate 10 having a size of 256 mm×182 mm and a thickness of 4 mm to create a step. Similarly, a single-sided black light-shielding tape 9 having a width of 15 mm and a thickness of 100 μm was laminated on the glass plate 10 to create a step. On top of these steps, a test piece 7 of double-sided adhesive tape having a width of 10 mm was laminated on the four sides of the glass plate 10. A glass plate 12 having a size of 256 mm×182 mm and a thickness of 1 mm was laminated on the test piece 7, and the glass plate 10 and the glass plate 12 were bonded together via the test piece 7. Furthermore, a single-sided black light-shielding tape 13 having a thickness of 100 μm was laminated on the glass plate 12 to obtain a sample for a surface waviness test. In accordance with JIS B0601:2001, the maximum height Sz of the surface roughness was measured for a measurement area 11 of 210 mm × 105 mm on the surface waviness test sample using a laser microscope (Keyence Corporation, VR-3000 type). The maximum height Sz was indicated as ⊚ when it was less than 120 μm, as ◯ when it was 120 μm or more and less than 200 μm, and as × when it was 200 μm or more.

[0103] [Table 1]

[0104] [Table 2] [Industrial Applicability]

[0105] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive tape that has excellent resistance to drop impact, can reduce display unevenness on a display device, and has a foam base material that can be easily torn when peeled off from an adherend. [Explanation of symbols]

[0106] 1 PC board 2 Test pieces (double-sided adhesive tape) 3. Wire 4 SUS board 5 PMMA board 6. Frame-shaped test piece (double-sided adhesive tape) 7 Test piece (double-sided adhesive tape) 8 Single-sided black light-shielding tape (width 15 mm, thickness 50 μm) 9. Single-sided black light-shielding tape (width 15 mm, thickness 100 μm) 10 Glass Plate 11 Measurement area 12 Glass Plate 13 Single-sided black light-shielding tape 18 Test piece (double-sided adhesive tape) 19 SUS board

Claims

1. A double-sided pressure-sensitive adhesive tape having a foam substrate and pressure-sensitive adhesive layers laminated on both sides of the foam substrate, The foam base material has a bubble volume fraction of 40% by volume or more and 75% by volume or less, and a shear breaking strength of 200 N / inch 2 (0.310N / mm 2 ) or more 500N / inch 2 (0.775 N / mm 2 ) or less and a thickness of 100 μm or more. A double-sided adhesive tape characterized by:

2. 2. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has a 25% compressive strength of 0.015 MPa or more and 0.08 MPa or less.

3. 3. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has an average major axis distribution of cells of 55 μm or less.

4. 4. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has a standard deviation of the major axis distribution of the cells of 30 [mu]m or less.

5. 5. The double-sided pressure-sensitive adhesive tape according to claim 1, 2, 3 or 4, wherein the foam substrate has air bubbles with an aspect ratio of 0.2 or less.

6. 6. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has bubbles with an aspect ratio of 1.5 or less.

7. 7. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has an open cell ratio of 95 volume % or less.

8. 8. The double-sided pressure-sensitive adhesive tape according to claim 1, wherein the foam substrate has a thickness of 1000 μm or less.

9. the pressure-sensitive adhesive layer is made of an acrylic pressure-sensitive adhesive containing an acrylic copolymer and a tackifier, and has a gel fraction of 1% by weight or more and 90% by weight or less; The acrylic copolymer contains a hydroxyl group, has a weight average molecular weight of 300,000 or more and 2,000,000 or less, and a molecular weight distribution (Mw / Mn) of 1.05 or more and 5.0 or less, The tackifier is a rosin-based resin containing a hydroxyl group or a terpene-based resin containing a hydroxyl group, and has a softening temperature of 70° C. or higher and 170° C. or lower and a hydroxyl value of 25 or higher and 160 or lower.

9. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7 or 8.

10. 10. The double-sided pressure-sensitive adhesive tape according to claim 1, further comprising a resin sheet on at least one side of the foam substrate, the resin sheet having a thickness of 10 μm or more and 100 μm or less.

11. 11. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, comprising a first resin sheet laminated on a first surface of a foam substrate and a second resin sheet laminated on a second surface of the foam substrate, wherein at least one selected from the group consisting of the first resin sheet and the second resin sheet is a resin sheet made of a thermoplastic resin.

12. 12. The double-sided pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11, wherein the thickness of the pressure-sensitive adhesive layer is from 20 μm to 100 μm.

13. 13. The double-sided adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, wherein the thickness of the double-sided adhesive tape is 100 μm or more and 1200 μm or less.

Citation Information

Patent Citations

  • Impact-absorbing tape

    JP2009242541A

  • Pressure-sensitive adhesive sheet for front plate of display device

    JP2009258274A

  • Pressure sensitive adhesive sheet for electronic apparatus

    JP2016023236A

  • Double-sided adhesive tape, method of making, method of use, and article assembled therefrom

    JP2017506683A

  • Adhesive tape

    JP2018154820A